Estudio sobre el barrido de vías públicas en la ciudad de Moyobamba 2011 - Pérez Fernández, Jhon Luis (2012)
This research project called profile thesis entitled "STUDY ON PUBLIC ROADS IN SWEEPING CITY MOYOBAMBA 2011" is basically the study of the current state of the whole system Scanning Municipal Solid Waste that is provided in the city Moyobamba, also to have a real diagnosis of the deficiencies in the service provided by the management and also to present a list of measures which will significantly improve the service. In addition to the implementation of the project in question allowed up technical information as regards: total length of paved pathways Moyobamba is 19,659 linear feet (19.6 Km) .The Scanning service that runs in our city; basically considered urban Moyobamba part of the same amounting to 11,082.7 linear feet, which in percentage terms represents 56.4% of people who enjoy Scanning Service; the average performance of each worker sweeper is 852.51 mt / sweeper / day, approx. 0.852 km / Sweeper / day. Solid Waste production is 47.52 metric tons per day produced by our Moyobamba. The type Collection is Conventional and Semi Conventional method is Sidewalks and corners and stroke to finish the collection that runs on Moyobamba is Comb and Double Comb. With the implementation of this thesis project we are contributing significantly to strengthen the environmental management of our province so, and it is therefore important to have a correct management of the entire system of Solid Waste Management Moyobamba.